Recombinant Proteins and Monoclonal Antibodies - Jefferis, Roy (Advances in biochemical engineering, biotechnology, 2021)
The human genome has become a subject of public interest, whilst the proteome remains the province of specialists. Less appreciated is the human glycoprotein (GP) repertoire (proteoglycome!); however, some 50% of open reading frame genes encode for proteins (P) that may accept the addition of N-linked and/or O-linked sugar chains (oligosaccharides). It is established that the attachment of defined oligosaccharide structures impacts mechanisms of action (MoAs), pharmacokinetics, pharmacodynamics, etc., and is a critical quality attribute (CQA) for recombinant GP therapeutics. The oligosaccharide structure attached at a given site may exhibit structural heterogeneity, and individual structures (glycoforms) may modulate MoAs. The biopharmaceutical industry is challenged, therefore, to produce recombinant GP therapeutics that have structural fidelity to the natural (endogenous) molecule, in non-human cells. Multiple production platforms have been developed that, in addition to the natural glycoform, may produce unnatural glycoforms, including sugar residues that can be immunogenic in human subjects. Following a general introduction to the field, this review discusses glycosylation of recombinant monoclonal antibodies (mAbs), the contribution of glycoforms to MoAs and the development of customised mAb therapeutic glycoforms to optimise MoAs for individual disease indications.